EFFECT OF COMPLIANCE TO SASRA REGULATIONS ON FINANCIAL PERFORMANCE OF SAVINGS AND CREDIT CO-OPERATIVES IN KENYA: - WANYOIKE, SERAH WANGUI WANYOIKE (My University, 2013)
Deposit Taking Saccos’ in Kenya are required to adhere to regulations set by SASRA within a period of four years which is ending in 2014. Despite the fact that SASRA regulations have been in operation for the last four years, the effects of compliance of the DTS to these regulations on their financial performance has not been established. Empirical studies have clearly avoided looking at specific aspects of these regulations particularly their effects on financial performance of the Saccos. Hence, the purpose of this study was to establish the impact of SASRA Regulations on Saccos’ financial performance in Nairobi County. More specifically, the study sought to investigate the effect on staff competence, quality of board of directors and corporate governance on financial performance of Saccos. The target population was all the 34 DTS in Nairobi County which were obtained through census using survey design. Both primary and secondary was used in this study. The researcher used data from 2006 to 2012 to carry out the research. Analysis of data was done using both descriptive and inferential statistics with aid of Statistical Package for Social Science (SPSS) computer software package. The study findings indicated that the quality of the Board of Directors was an important aspect in improving the Saccos financial performance as per the SASRA regulations (β = 0.567; p=0.05). The findings also revealed that Sacco staff competence (β = 0.705; p=0.05) had a strong influence on the financial performance of the Saccos in the area. Corporate governance (β = 0.778; p =0.05) was also identified as the most significant effect of SASRA regulations on the Saccos financial performance. The study concludes that all the variables of the study were important factors in financial performance of the Saccos and needed to be addressed beginning with the most crucial which was in this case corporate governance. It is recommended that the SASRA regulations should be modified to upgrade the roles and qualifications of the Board members in order for them to play amore influential role in improving the financial performance of the Saccos and more staff should be involved in decision making at higher levels at some point in their careers in order to develop their potential as future managers and directors of the Saccos. Further research should be done in the following areas; the effect of competition on the financial performance of the Saccos and the effect of SASRA regulations on the organizational culture of Saccos. The significance of this study is that if this study was never conducted, the stakeholders would never have known the influence that corporate governance, staff competence and quality board has on the financial performance of Saccos.
Keywords: EFFECT OF COMPLIANCE TO SASRA REGULATIONS